Peran Manajemen Pendidikan Dalam Membina Kompetensi Sosial Tenaga Kependidikan di Kabupaten Ende - Damianus Tola; Djou Sewa Adrianus (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
Satisfaction of services provided to students, to improve the quality of learning, the role of the principal is very decisive. The principal's creativity and strategy is to apply all the ideas or ideas of teachers that have been obtained from the results of the teacher's meeting to make a real work to be able to master the competencies and abilities of educators as part of communicating and interacting effectively with students and fellow education staff, parents and guardians, the community. around it becomes an agent of social change. Leaders are responsible and accountable for certain jobs successfully, and evaluate how well, teachers and education personnel carry out the tasks that must be completed, if they find tasks that have not been completed within the specified time it is a failure and this is a direct reflection of success. or failure of school leaders